A) ( ₁/₄ x² - o,2y -3 ) - ( - ₁/₅y + 0,25x² - 3 ) =

b)( 1,2xy - 8y² ) - ( -5xy + 10 ₁/₂y² - 8,3 ) - ( - 2,3 + 3,8xy ) =

c) ( 3 ₁/₂x² - 7,5y ) -5 - ( 1 ₁/₂y + 5,5x² - 3,2 ) + 2x² + 9y =

d) -3,2x + ( - 0,8y +2z ) - ( 1,2y - 0,8x ) - ( 2z - 2,4x ) =

e) ( 4a² - 3ab - 0,1a ) + ( - 14a² + 2ab + o,1a ) =



Proszę o pomoc.
To jest moja praca domowa na jutro ,

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-03T18:24:23+01:00
A) ( ₁/₄ x² - o,2y -3 ) - ( - ₁/₅y + 0,25x² - 3 ) = ¼x²-⅕y-3+⅕y-¼x²+3=0

b)( 1,2xy - 8y² ) - ( -5xy + 10 ₁/₂y² - 8,3 ) - ( - 2,3 + 3,8xy ) =
1,2xy-8y²+5xy-10½y²+8,3+2,3-3,8xy=2,4xy-18,5y²+10,6

c) ( 3 ₁/₂x² - 7,5y ) -5 - ( 1 ₁/₂y + 5,5x² - 3,2 ) + 2x² + 9y =
3½x²-7,5y-5-1½y-5,5x²+3,2+2x²+9y=-1,8


d) -3,2x + ( - 0,8y +2z ) - ( 1,2y - 0,8x ) - ( 2z - 2,4x ) =
-3,2x - 0,8y +2z-1,2y+0,8x-2z+2,4x=-2y

e) ( 4a² - 3ab - 0,1a ) + ( - 14a² + 2ab + o,1a ) =4a² - 3ab - 0,1a - 14a² + 2ab + o,1a=-10a²-ab=a(-10a-b)